Students’ Abilities and Difficulties in Comprehending English Reading Texts at Secondary Schools; An Effect of Phonemic Awareness - Edi Firman; Haerazi Haerazi; Sadaf Dehghani (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
Reading comprehension in the EFL context requires abilities not only linguistic competences but also reading strategies. The timely acquisition of this competence has a crucial effect for language learners. Unfortunately, most language learners in all level have low skills and high difficulties to acquire reading skills. This study aims to explore students’ abilities and difficulties in comprehending English reading texts as secondary level. This study is categorized as qualitative study consisting of three main data gathering methods: semi-structured interviews, classroom observations, and group discussions. The data collected then are analyzed in stages, namely data condensation, data display, and data conclusion. Based on the result of analysis, this study showed that students have low reading achievement at secondary level. The low achievement is affected by some reading difficulties such as low reading exercises, unwilling to read out loud, low reading skills, low vocabulary, low phonemic awareness, low reading strategies, and low grammatical competence. For further studies, reading exercises and phonemic awareness in reading activities should be paid intention with giving students with various reading texts to train them comprehend EFL texts.